Reconceptualizing and modeling sustainable consumption behavior: A synthesis of qualitative evidence from online education industry - Songyu Jiang; Ruihui Pu (Innovative Marketing)
In recent years, the concept of sustainable consumption behavior (SCB) is largely introduced and changed continuously to be discussed with industries such as energy sector, agriculture, transportation, sharing economy, and tourism. However, the study of sustainable consumption behavior in the online education industry (SCBOEI) remains a research gap. Thus, this paper aims to identify the significance of sustainable consumption behavior and theoretically conceptualize SCBOEI. This study employs content and text analysis to reconceptualize the major theories that contribute to the research of SCB. The findings in this study show that SCBOEI is contributed of great significance to promote sustainable development. In addition, this study introduces a model of SCBOEI, in which the consumer value theory, social exchange theory, and planned behavior theory are integrated. Additionally, this paper suggests that value, environmental attitude, identity, consumer engagement, and contextual factors (government behavior, market conditions, and environmental education) are highly important to extend the research on SCBOEI. In conclusion, this study strongly recommends that SCB research shall be directed to the online education industry. Furthermore, future studies shall emphasize the empirical effects of psychological factors, activity factors, and contextual factors for SCBOEI to find the correlation.